Data Standards In The Context Of National Geoinformation Infrastructure - Kayastha, Durgendra Man (Journal on Geoinformatics, Nepal, 2007)
Development of GIS related activities and acquisition of data on spatial variables using remotely sensed data as well as maps have provided new insights in the field of decision-making concerning development planning and administration of natural resources. With the availability of software tools collection of geographic data for a particular application has become so easy that each institution can generate data on its own. Such an approach would lead to confusion among users, owing to differences in data format, reliability of data and most of all consistency of data could not be maintained due to redundancy. The paper outlines importance of geoinformation infrastructure and its components, followed by outlining areas where standards can be defined on basic elements of geospatial data such as geo-referencing, data definition, metadata etc. The paper also provided an overview of NTDB.